Pemanfaatan Sekam Padi (Oryza sativa) Dan Cangkang Kerang Totok (Geloina sp.) Sebagai Bahan Campuran Paving Block: Utilization of Rice Husks (Oryza sativa) and Totok Shells (Geloina sp.) as Paving Block Mixtures - Ma’ruf, Nazula Azzam; Prasadi, Oto; Dwityaningsih, Rosita (Media Ilmiah Teknik Lingkungan (MITL), 2024)
Shellfish shells and rice husks can be processed into charcoal and ash. Shellfish ash and rice husk charcoal contain chemical compounds such as pozzolan, lime (CaO), alumina and silica compounds which can replace cement in paving block mixtures. The use of rice husk charcoal and full-blooded clam shell ash as an alternative provides stronger pressure resistance. This research aims to determine the effect of the composition of a mixture of shell ash and rice husk charcoal on the quality of paving blocks. The results of this research were a mixture of composition A3 (2:1) with 66.6 grams of rice husks and 33.3 grams of full-blooded clam shells as well as 500 grams of cement and 1500 grams of sand, resulting in a compressive strength of 14.3 Mpa and was classified as C. Composition A5 (3:1) mixture with 25 grams of rice husks and 75 grams of full-blooded clam shells as well as 500 grams of cement and 1500 grams of sand, produces a compressive strength of 16.7 Mpa and is classified as B. Meanwhile, the composition of the A0 (0:0) mixture without A mixture of rice husks and shells only produces a compressive strength of 9.05 Mpa and is classified as D. The conclusion of the research is that paving blocks of composition A5 show the best water absorption quality with water absorption results of 7.69%.